Initial UK Experience of Stereotactic Body Radiotherapy for Extracranial Oligometastases: Can We Change the Therapeutic Paradigm?. Issue 7 (July 2015) - Aitken, K.; Tree, A.; Thomas, K.; Nutting, C.; Hawkins, M.; Tait, D.; Mandeville, H.; Ahmed, M.; Lalondrelle, S.; Miah, A.; Taylor, A.; Ross, G.; et al.
Abstract Aims To retrospectively review the toxicity and early outcome data from patients who have received stereotactic body radiotherapy (SBRT) for extracranial oligometastases at a single UK institution. Materials and methods Eligible patients had ≤3 extracranial metastases and performance status ≤2. Prior systemic therapy and radical treatment of oligometastastic relapse with any standard treatment modality was permitted. Patients with synchronous metastatic disease were excluded unless they had evidence of controlled primary disease after radical therapy. Follow-up consisted of clinical examination, biochemical and radiological assessments in accordance with standard clinical care. Progression events were defined using RECIST. Toxicity was evaluated using CTCAE v4.0. Local control, progression-free survival (PFS), freedom from widespread distant metastasis (defined as disease not amenable to further radical salvage therapy) and overall survival were calculated. Results Between July 2011 and April 2014, 73 patients with 87 metastases received SBRT (range 1–3 per patient). The median follow-up was 14.5 months (range 0–26.4). The median PFS was 14.5 months (1 year PFS 57%, 2 year 28%); 1 year overall survival 96%, 2 year 79.8%; 2 year local control 88%. At 2 years, 46% of patients were free from widespread distant metastases. No ≥ grade 3 acute or late toxicity was observed. Conclusion At this time point, observed toxicity is minimal with excellent local control rates. This promising treatment paradigm requires further investigation in the context of a randomised controlled trial to establish if the addition of SBRT to standard care improves survival outcomes.